Can telemedicine help integrate the referral-based healthcare system? An economic and operational analysis - Xuejing Cao; Guohao Li; Heng Zhao (PLoS ONE, 2025)
Purpose Telemedicine can help specialists in providing efficient care to patients from a distance and it has been growing steadily in healthcare. This study aims to provide an operational perspective by investigating the effect of telemedicine on patients’ choices, healthcare providers’ service decisions, service quality and total social welfare. Methods We propose an optimization model that incorporates patients’ choices and physicians’ actions under two scenarios: full coverage and partial coverage. We analyze the model and conduct numerical experiments to explore the impact of telemedicine in a referral-based healthcare system with heterogeneous patients. Results The findings show that telemedicine can induce greater collaboration between generalists and the specialist, which would result in the specialist spending less time on each patient. Interestingly, we find that after the introduction of telemedicine, the average quality cost decreases under full coverage but increases under partial coverage. Moreover, the introduction of telemedicine could lead to higher social welfare as it improves the accessibility of services to patients, especially in rural areas. Finally, this study also demonstrates that the referral-based healthcare system may benefit more from telemedicine when there is a heavier travel burden for patients or a higher financial incentive for generalists. Conclusion The introduction of telemedicine mainly contributes to the patients’ service accessibility, particularly for patients in remote areas, and can foster closer collaboration between generalists and specialists. However, in hospitals where medical resources are already strained, it may worsen specialist overuse and lead to lower service quality. These findings highlight that telemedicine is not universally beneficial. The policymaker should consider regional coverage conditions and use targeted financial incentives to improve its effectiveness within referral-based healthcare systems.